3D printed artificial cornea for corneal stromal transplantation. (15th June 2020) - Ulag, Songul; Ilhan, Elif; Sahin, Ali; Karademir Yilmaz, Betul; kalaskar, Deepak M.; Ekren, Nazmi; Kilic, Osman; Nuzhet Oktar, Faik; Gunduz, Oguzhan
Graphical abstract: Highlights: 3D printing process is a promising technology to obtain cornea structure. 3D-printed corneal stroma constructs can withstand intraocular pressure. PVA/Chitosan blends had high potential for corneal tissue engineering structures. Abstract: The aim of this study is to understand the optical, biocompatible, and mechanical properties of chitosan (CS) and polyvinyl-alcohol (PVA) based corneal stroma constructs using 3D printing process. Corneal stroma is tested for biocompatibility with human adipose tissue-derived mesenchymal stem cells (hASCs). Physico-chemical and chemical characterization of the construct was performed using scanning electron microscopy (SEM), fourier transforms infrared spectroscopy (FTIR). Optical transmittance was analyzed using UV-Spectrophotometer. Results showed fabricated constructs have required shape and size. SEM images showed construct has thickness of 400 µm. The FTIR spectra demonstrated the presence of various predicted peaks. The swelling and degradation studies of 13%(wt)PVA and 13%(wt)PVA/(1, 3, 5)%(wt)CS showed to have high swelling ratios of 7 days and degradation times of 30 days, respectively. The light transmittance values of the fabricated cornea constructs decreased with CS addition slightly. Tensile strength values decreased with increasing CS ratio, but we found to support intraocular pressure (IOP) which ranges from 12 to 22 mm-Hg. Preliminary biostability studies showed that composite constructs were compatible with hASCs even after 30 days' of degradation, showing potential for these cells to be differentiated to stroma layer in future. This study has implications for the rapid and custom fabrication of various cornea constructs for clinical applications.